Analisis Strategi Promosi dalam Meningkatkan Penjualan Makanan Cepat Saji pada Ayam Bersih Berkah Cabang Citeureup - Puput Amelia Puspita; Riyan Hadithya (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the promotional strategies implemented by Ayam Bersih Berkah Citeureup in increasing sales of fast food products. In the face of fierce competition in the culinary industry, Ayam Bersih Berkah utilizes various promotional elements, both online and offline. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and direct documentation in the field. The results of the study show that Ayam Bersih Berkah implements a promotional strategy with six elements of the promotional mix, namely advertising, sales promotion, public relations, personal sales, direct marketing, and digital marketing. Digital promotion through social media such as Instagram and WhatsApp is the most influential strategy in reaching consumers and increasing daily sales volume. In addition, sales promotions such as discounts and product bundling are able to attract new consumers and encourage repeat purchases, especially at certain moments such as weekends or holidays. Advertising is done in a simple but consistent manner, especially by utilizing digital media that is cost-effective and easily accessible. Public relations are built through engagement with local communities and repeat customers, although they are still not managed to the maximum. Personal sales can also be seen from the way employees serve customers in a friendly manner and provide product recommendations directly. Direct marketing is carried out by distributing brochures and promos through short message applications. However, in its implementation, there are still several obstacles such as limited promotional budgets, lack of consistency in marketing campaigns, and not optimal public relations activities that can build a sustainable brand image. Therefore, continuous evaluation and improvement are needed so that the promotional strategy carried out can be maximized in increasing sales and customer loyalty.